2023
DOI: 10.1038/s41467-023-36997-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease

Abstract: The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…A wider angle (greater than 100 degrees) is usually associated with changes in the Twave axis rather than QRS related and carries a considerably increased cardiac risk [30]. Reasons for θ RT angle changes are associated to changes in ventricular repolarization itself, or secondary to conduction abnormalities [31], [32]. A wide spatial θ RT angle has been demonstrated to be a predictor of sudden cardiac death in the general population (low risk) and in groups considered to be at higher risk (clinical population) and a strong predictor of all-cause mortality in postmenopausal women [30], [32], [33].…”
Section: A Angular Variability Analysis In Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A wider angle (greater than 100 degrees) is usually associated with changes in the Twave axis rather than QRS related and carries a considerably increased cardiac risk [30]. Reasons for θ RT angle changes are associated to changes in ventricular repolarization itself, or secondary to conduction abnormalities [31], [32]. A wide spatial θ RT angle has been demonstrated to be a predictor of sudden cardiac death in the general population (low risk) and in groups considered to be at higher risk (clinical population) and a strong predictor of all-cause mortality in postmenopausal women [30], [32], [33].…”
Section: A Angular Variability Analysis In Simulationmentioning
confidence: 99%
“…Both QRS and Twave angles changed from control to deformed simulations without considering ventricular conduction abnormalities in the deformed model. A recent genome-wide association study showed that ventricular conduction abnormalities are the most likely cause of QRS-T angle widening, being able to counteract the reduction in θ RT-XY [31]. As far as we know, there have been no studies indicating that conduction abnormalities occur as a result of IUGR.…”
Section: A Angular Variability Analysis In Simulationmentioning
confidence: 99%